Basques on the BBC: exile, radio and propaganda (1941–1956) - Arrieta, Leyre (Historia y Comunicación Social, 2025)
The aim of this article is to explain the involvement of Basques exiles in the British Broadcasting Corporation (BBC) between 1941 and 1956. The research, which has used unpublished sources from four Basque archives, concludes that this radio collaboration responded to the propaganda strategies of both the Foreign Office and the Basque Government. The different international political contexts determined the nature of this cooperation, so that two distinct periods can be distinguished: the years of the Second World War, in which Basque representation was personified in the person of Canon Alberto Onaindia, and the years between 1947 and 1956, in which brief broadcasts were made in Basque as part of the Spanish Program. This study fills a gap in the literature on Basque broadcasting and on the BBC's external services.
Keywords: Basque exile; Franco dictatorship; BBC; Basque language; radio